An Integrated Hydraulic-Hormonal Model of Conifer Stomata Predicts Water Stress Dynamics. Issue 2 (24th March 2017) - Deans, Ross M.; Brodribb, Timothy J.; McAdam, Scott A.M.
Abstract : A simple model combining leaf hydraulics and abscisic acid sensitivity can predict stomatal dynamics to short-term changes in plant water status in a conifer.